Metode Semantik vs. Metode Komunikatif: Studi Kasus Penerjemahan dari Bahasa Indonesia ke Bahasa Inggris - Dewi, Haru Deliana (Jurnal Penerjemahan, 2023)
Translation methods by Newmark (1988) have long been known among translation academicians and perhaps by a small number of translation practitioners. However, the clear differences between one method and another, especially between semantic and communicative translation methods as the most ideal methods, have not been shown indepth and in detail for the Indonesian and English language pair translation. Therefore, this paper aims to provide a translation analysis to show the differences in the application of those two methods. This study applies a descriptive qualitative approach in analyzing an academic text translation which contains both translation methods. The results show the semantic method is applied in the explanation with no figurative language and little or no cultural content, while the communicative method is applied in expressions full of cultural content. Therefore, with the semantic method, the meanings and the messages between the Source Text (ST) and the Target Text (TT) are quite close, whereas with the communicative method, the meanings of the ST and the TT are quite different despite having the same messages. Keywords:semantic method; communicative method; translation methods; the Indonesian and English language pair.